Mirror trends of plasticity and stability indicators in primate prefrontal cortex. (4th October 2017) - García‐Cabezas, Miguel Á.; Joyce, Mary Kate P.; John, Yohan J.; Zikopoulos, Basilis; Barbas, Helen
Abstract: Research on plasticity markers in the cerebral cortex has largely focused on their timing of expression and role in shaping circuits during critical and normal periods. By contrast, little attention has been focused on the spatial dimension of plasticity–stability across cortical areas. The rationale for this analysis is based on the systematic variation in cortical structure that parallels functional specialization and raises the possibility of varying levels of plasticity. Here, we investigated in adult rhesus monkeys the expression of markers related to synaptic plasticity or stability in prefrontal limbic and eulaminate areas that vary in laminar structure. Our findings revealed that limbic areas are impoverished in three markers of stability: intracortical myelin, the lectin Wisteria floribunda agglutinin, which labels perineuronal nets, and parvalbumin, which is expressed in a class of strong inhibitory neurons. By contrast, prefrontal limbic areas were enriched in the enzyme calcium/calmodulin‐dependent protein kinase II (CaMKII), known to enhance plasticity. Eulaminate areas have more elaborate laminar architecture than limbic areas and showed the opposite trend: they were enriched in markers of stability and had lower expression of the plasticity‐related marker CaMKII. The expression of glial fibrillary acidic protein (GFAP), a marker of activated astrocytes, was also higher in limbic areas, suggesting that cellular stress correlates with the rate of circuit reshaping. Elevated markers of plasticity may endow limbic areas with flexibility necessary for learning and memory within an affective context, but may also render them vulnerable to abnormal structural changes, as seen in neurologic and psychiatric diseases. Abstract : Systematic variation in cortical structure across areas suggests varying levels of plasticity. Here, we show that in prefrontal cortices of adult monkeys, markers related to synaptic plasticity are high in limbic areas, while markers of stability are low; the opposite trend is seen in eulaminate areas, which have greater laminar elaboration than limbic areas. High plasticity markers may render limbic areas flexible for learning and memory but also vulnerable to neurologic and psychiatric diseases.